P-COSCA (Pediatric Core Outcome Set for Cardiac Arrest) in Children: An Advisory Statement From the International Liaison Committee on Resuscitation. Issue 16 (20th October 2020) - Topjian, Alexis A.; Scholefield, Barnaby R.; Pinto, Neethi P.; Fink, Ericka L.; Buysse, Corinne M.P.; Haywood, Kirstie; Maconochie, Ian; Nadkarni, Vinay M.; de Caen, Allan; Escalante-Kanashiro, Raffo; Ng, Kee-Chong; Nuthall, Gabrielle; et al.
Abstract : Studies of pediatric cardiac arrest use inconsistent outcomes, including return of spontaneous circulation and short-term survival, and basic assessments of functional and neurological status. In 2018, the International Liaison Committee on Resuscitation sponsored the COSCA initiative (Core Outcome Set After Cardiac Arrest) to improve consistency in reported outcomes of clinical trials of adult cardiac arrest survivors and supported this P-COSCA initiative (Pediatric COSCA). The P-COSCA Steering Committee generated a list of potential survival, life impact, and economic impact outcomes and assessment time points that were prioritized by a multidisciplinary group of healthcare providers, researchers, and parents/caregivers of children who survived cardiac arrest. Then expert panel discussions achieved consensus on the core outcomes, the methods to measure those core outcomes, and the timing of the measurements. The P-COSCA includes assessment of survival, brain function, cognitive function, physical function, and basic daily life skills. Survival and brain function are assessed at discharge or 30 days (or both if possible) and between 6 and 12 months after arrest. Cognitive function, physical function, and basic daily life skills are assessed between 6 and 12 months after cardiac arrest. Because many children have prearrest comorbidities, the P-COSCA also includes documentation of baseline (ie, prearrest) brain function and calculation of changes after cardiac arrest. Supplementary outcomes of survival, brain function, cognitive function, physical function, and basic daily life skills are assessed at 3 months and beyond 1 year after cardiac arrest if resources are available. Abstract : Supplemental Digital Content is available in the text.